Exposing Flaws of Affirmative Consent through Contemporary American Teen Films. Issue 1 (1st March 2021) - Meek, Michele
Abstract: The discursive shift during the twenty-first century from "no means no" to "yes means yes" clearly had an impact on contemporary American teen films. While teen films of the 1970s and 1980s often epitomized rape culture, teen films of the 2010s and later adopted consent culture actively. Such films now routinely highlight how obtaining a girl's "yes" is equally important to respecting her "no." However, the framework of affirmative consent is not without its flaws. In this article, I highlight how recent teen movies expose some of these shortcomings, in particular how affirmative consent remains a highly gendered discourse that prioritizes verbal consent over desire.